The expression level of small non‐coding RNAs derived from the first exon of protein‐coding genes is predictive of cancer status. (17th February 2014) - Zovoilis, Athanasios; Mungall, Andrew J; Moore, Richard; Varhol, Richard; Chu, Andy; Wong, Tina; Marra, Marco; Jones, Steven JM
Synopsis <boxed-text content-type="graphic" id="embr201337950-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> The expression of small non‐coding RNAs encoded within the first exon of genes can be used to efficiently identify cancer samples and classify patients into subgroups of different survival. Such pan‐cancer association is the first link between these RNAs and disease. Exon 1 small non‐coding RNAs (smRNAs) can distinguish between cancer and normal tissues. The prediction potential of exon 1 smRNAs differs from that of other smRNAs around transcriptional start sites (TSS). smRNA locations around TSS are conserved between different individuals. smRNA locations are enriched within CpG islands and their levels negatively correlated with DNA methylation.